Polymorphisms in Genes Encoding Glutathione Transferase Pi and Glutathione Transferase Omega Influence Prostate Cancer Risk and Prognosis - Santric, Veljko; Dragicevic, Dejan; Matic, Marija; Djokic, Milica; Pljesa-Ercegovac, Marija; Radic, Tanja; Suvakov, Sonja; Nikitovic, Marina; Stankovic, Vesna; Milojevic, Bogomir; Radovanovic, Milan; Dzamic, Zoran; et al. (Frontiers in Molecular Biosciences, 2021)
Considering pleiotropic roles of glutathione transferase (GST) omega class members in redox homeostasis we hypothesized that polymorphisms in GSTO1 and GSTO2 might contribute to prostate cancer (PC) development and progression. Therefore, we performed a comprehensive analysis of GSTO1 and GSTO2 SNPs role in susceptibility to PC, as well as whether they might serve as prognostic biomarkers independently or in conjunction with other common GST polymorphisms (GSTM1, GSTT1, GSTP1). Genotyping was performed in 237 PC cases and 236 age-matched controls by multiplex PCR for deletion GST polymorphisms and quantitative PCR for SNPs. The results of this study, for the first time, demonstrated that homozygous carriers of both GSTO1*A/A and GSTO2*G/G variant genotypes are at increased risk of prostate cancer. This was further confirmed by haplotype analysis, which showed that H2 comprising both variant GSTO1*A and GSTO2*G alleles represented a high-risk combination. However, prognostic relevance of polymorphisms in GST omega genes was not found in our cohort of PC patients. Analysis of the role of other investigated GSTs polymorphisms (GSTM1, GSTT1, GSTP1) in terms of PC prognosis has shown shorter survival in carriers of GSTP1*T/T (rs1138272) genotype compared to those carrying at least one referent allele. In addition, presence of GSTP1*T/T genotype independently predicted four-fold higher risk of overall mortality among PC patients. This study demonstrated significant prognostic role of GST polymorphism in PC.